2018
DOI: 10.24818/jamis.2018.01001
|View full text |Cite
|
Sign up to set email alerts
|

How has IFRS impacted financial reporting for unlisted entities?

Abstract: This paper addresses the question whether adoption of International Financial Reporting Standards (IFRS) is associated with low earnings management in unlisted companies in three European countries. Therefore, this paper investigates whether companies that have adopted IFRS voluntarily engage significantly less in earnings management compared to companies that have not adopted IFRS. Moreover, this study examines firm-specific incentives and their role in the adoption decision within different institutional set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
1
0
1
Order By: Relevance
“…This result supports the hypothesis that companies with a large size have a higher level of compliance with IFRS than small ones do. This finding is consistent with many studies conducted around the world (Al-Shammari et al , 2008; Aljifri and Khasharmeh, 2006; Dumontier and Raffournier, 1998; Floropoulos, 2006; García Benau and Zorio Grima, 2002; Guerreiro et al , 2008; Haapamäkia, 2018; Jaafar and McLeay, 2007), which have observed similar associations between firm size and compliance with international standards. In the current study, larger companies in the NA region adopted international standards more frequently than smaller ones.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This result supports the hypothesis that companies with a large size have a higher level of compliance with IFRS than small ones do. This finding is consistent with many studies conducted around the world (Al-Shammari et al , 2008; Aljifri and Khasharmeh, 2006; Dumontier and Raffournier, 1998; Floropoulos, 2006; García Benau and Zorio Grima, 2002; Guerreiro et al , 2008; Haapamäkia, 2018; Jaafar and McLeay, 2007), which have observed similar associations between firm size and compliance with international standards. In the current study, larger companies in the NA region adopted international standards more frequently than smaller ones.…”
Section: Resultssupporting
confidence: 92%
“…Accounting, as a tool of communication for business, is likely to be applied dissimilarly around the world (Barbu et al , 2014; Haapamäkia, 2018; Macve, 2014). This may be because of differences in environment, such as history, politics, economy and other aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Hoje em dia o tema da qualidade da informação financeira não perdeu a sua atualidade havendo vários autores que demonstram que o assunto da qualidade da informação contida nas demonstrações financeiras tem estado patente na literatura nacional e internacional, [15] [10] [21] [48].…”
Section: Introductionunclassified